IDENTIFYING AND FIXING UX-FRICTION EMPLOYEE DEVELOPMENT WEBSITE WITH MIXED APPROACH HEART FRAMEWORK AND USABILITY TESTING - Rini W; Liptia Venica; Rizki Hikmawan (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2024)
The company website has an important role in the business processes that occur in the company, one of which is managing employee productivity. PT.XYZ utilizes the Kaizen website to improve the quality of its employees. Assessment of user experience while operating the website can be a form of evaluation between expectations and actual conditions related to website feasibility. In this study, the researcher intends to find out what indicators are obstacles in the operation of a web-based application called the Kaizen website at PT.XYZ so that there is inefficiency in its use. This research involved 54 respondents who were employees of PT.XYZ. The combination of HEART and Usability Testing methods is used to identify obstacles experienced by users and evaluate user experience when using the Kaizen website. The results of the analysis are then used to improve website performance in order to create a good user experience. The results showed that the HEART score increased by an average of 9% on each variable. Usability testing assessment also shows that the Kaizen website reaches the acceptable category with a score of 90.5 after improvements are made.